2014
DOI: 10.1016/j.ijid.2013.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility profiles and correlation with pneumococcal serotypes soon after implementation of the 10-valent pneumococcal conjugate vaccine in Brazil

Abstract: Our population of pneumococci represents a transition era, soon after the introduction of PCV10. Non-susceptible patterns were found to be associated with classical PCV serotypes (especially serotype 14), which is still highly prevalent, and non-PCV10 ones (19A), which may disseminate, occupying the biological niche left by the vaccine serotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 27 publications
3
7
1
2
Order By: Relevance
“…This means that, theoretically, patients receiving the vaccine combination would have a reduction in the number of IPD cases associated with the serotypes identified in the present study. Andrade et al 18 and Mott et al 16 ) reported a theoretical coverage of PCV13 of 94.1% and 64.5%, respectively, which is well above our results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This means that, theoretically, patients receiving the vaccine combination would have a reduction in the number of IPD cases associated with the serotypes identified in the present study. Andrade et al 18 and Mott et al 16 ) reported a theoretical coverage of PCV13 of 94.1% and 64.5%, respectively, which is well above our results.…”
Section: Discussionsupporting
confidence: 90%
“…In 1988, the first case of resistance to penicillin was reported in Brazil, 22 ) and, in 2006, Camargos et al published that the 7-valent pneumococcal conjugate vaccine covered 89% of penicillin-resistant pneumococci and could then help reduce the spread of these strains, thereby decreasing the need for antibiotics. 23 Regardless of the existence of vaccines, increased pneumococcal resistance to penicillin has become worrisome, 16 ) and, in the future, therapeutic failure may occur when starting empirical antimicrobial therapy. 24 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is well described that antimicrobial resistance rates depend on the geographic region of the isolate. Research conducted in southern Brazil demonstrated 159 S. pneumoniae isolates from invasive sites; among all samples, 152 (95.6%) of the isolates were susceptible to β‐lactam agents . In our study, we emphasize the need to recognize markers of penicillin susceptibility in PPE.…”
Section: Discussionmentioning
confidence: 66%
“…Research conducted in southern Brazil demonstrated 159 S. pneumoniae isolates from invasive sites; among all samples, 152 (95.6%) of the isolates were susceptible to β-lactam agents. 38 In our study, we emphasize the need to recognize markers of penicillin susceptibility in PPE. We observed amplification of the wild-type pbp2b gene, indicating susceptibility, in 87.5% of patients; all patients negative for pbp2b had their treatment changed to non-β-lactam antibiotics.…”
Section: Resultsmentioning
confidence: 92%
“…Nos países em desenvolvimento, é comum encontrar também os sorotipos 1 e 5 em adultos (Mangtani et al, 2003). (Mott et al, 2013).…”
Section: Epidemiologiaunclassified